Method for producing super absorbent polymer
Patent Information
- Application Number
- JP2023124743
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0010】 本発明によれば、使用済み吸収性物品に含まれる吸水性樹脂、吸水性樹脂製造工程中の廃棄吸水性樹脂などの本来廃棄すべき吸水性樹脂を使用して、吸水性能(特に加圧下吸水倍率)を改善した吸水性樹脂を製造することができる。
Smart Images

Figure 2025021047000001 
Figure 2025021047000002 
Figure 2025021047000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a water-absorbent resin. In particular, the present invention relates to a method for producing a water-absorbent resin, in which a water-absorbent resin contained in a used absorbent article or a decomposition product of a water-absorbent resin obtained by decomposing a waste material during a water-absorbent resin production process is used as a part of a raw material during the production of the water-absorbent resin. [Background technology]
[0002] Super absorbent polymers (SAP) are water-swellable, water-insoluble polymer gelling agents that are used in a variety of absorbent products, including disposable diapers, sanitary napkins, adult incontinence products (incontinence pads), hygiene materials (sanitary products) such as pet sheets, soil water retention agents for agricultural and horticultural use, and industrial water-stopping agents.
[0003] Among these, the main applications of water-absorbent resins are sanitary materials such as disposable diapers and sanitary napkins. After being used for a short period of time (at most about one day), these sanitary materials are discarded in large quantities as used absorbent articles and incinerated.
[0004] In recent years, from the viewpoint of environmental protection, attempts have been made to recycle such used absorbent articles. For example, sanitary materials contain raw materials such as pulp, nonwoven fabric, adhesives, etc. in addition to the above-mentioned water-absorbent resin, and material recycling has been attempted in which these raw materials are separated from used sanitary materials and reused. Furthermore, a technology has been developed to recycle decomposition products of water-absorbent resin obtained from sanitary products for the manufacture of water-absorbent resin (Patent Documents 1-2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 213298 [Patent Document 2] International Publication No. 2022 / 080342 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the water-absorbing performance (particularly, water absorption capacity under pressure) of the water-absorbing resin obtained by recycling the decomposition product of the water-absorbing resin by the above-mentioned technique is not sufficient, and further improvement is required.
[0007] Therefore, the present invention has been made in consideration of the above circumstances, and aims to provide a technique for improving water absorption performance (particularly, water absorption capacity under pressure) when producing a water absorbent resin using a water absorbent resin that should be discarded, such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin production process. [Means for solving the problem]
[0008] The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, they have found that, when a water absorbent resin is produced using a decomposition product of a water absorbent resin obtained by decomposing a recovered water absorbent resin such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin production process as a part of a raw material, the decomposition product of the water absorbent resin is incorporated by a chemical method into a crosslinked water absorbent resin structure obtained by polymerizing a monomer constituting the water absorbent resin as a raw material, and have thus completed the present invention.
[0009] That is, the above-mentioned object can be achieved by a method for producing a water-absorbent resin, which comprises producing a water-absorbent resin by using a decomposed product of the water-absorbent resin obtained by decomposing a recovered water-absorbent resin as a part of a raw material, and is characterized in that the decomposed product of the water-absorbent resin is incorporated by a chemical method into a crosslinked structure of the water-absorbent resin obtained by polymerizing a monomer constituting the water-absorbent resin as a raw material. Effect of the Invention
[0010] According to the present invention, a water absorbent resin having improved water absorption performance (particularly, water absorption capacity under pressure) can be produced by using a water absorbent resin that should be discarded, such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin production process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] One aspect of the present invention relates to a method for producing a water-absorbent resin, which comprises producing a water-absorbent resin by using a water-absorbent resin decomposition product obtained by decomposing a recovered water-absorbent resin as a part of a raw material, and is characterized in that the water-absorbent resin decomposition product is incorporated by a chemical method into a water-absorbent resin crosslinked structure (particularly a water-absorbent resin crosslinked gel structure) obtained by polymerizing a monomer constituting the water-absorbent resin as a raw material. With this configuration, even when a water-absorbent resin is produced by using a water-absorbent resin that should be discarded, such as a water-absorbent resin contained in a used absorbent article or a water-absorbent resin that should be discarded during a water-absorbent resin production process, as a part of the raw material, a water-absorbent resin having improved water-absorption performance (particularly, water absorption capacity under pressure) can be produced.
[0012] In this specification, a "water-absorbent resin decomposition product" is also simply referred to as a "decomposition product" or a "decomposition product according to the present invention". A "water-absorbent resin crosslinked structure obtained by polymerizing a monomer as a raw material" is also simply referred to as a "crosslinked structure" or a "crosslinked structure according to the present invention". A "water-absorbent resin produced by the method of the present invention" is also simply referred to as a "water-absorbent resin" or a "water-absorbent resin according to the present invention".
[0013] The water absorbent resin obtained by adding a decomposition product of a water absorbent resin as in the technology of Patent Documents 1 and 2 has a problem that the water absorption properties, particularly the water absorption capacity under pressure, are lower than that of a normal water absorbent resin to which no decomposition product of a water absorbent resin is added. When the present inventors conducted research on the above problem, they found that the water absorbent resin using a decomposition product of a water absorbent resin as a part of the raw material tends to have a large amount of water-soluble matter (soluble polymer amount), and they presumed that this is one of the causes of the decrease in the water absorption properties, particularly the water absorption capacity under pressure, of the produced water absorbent resin. The present inventors further conducted intensive research on the reduction of the water-soluble matter. As a result, they presumed that the presence of the decomposition product of the water absorbent resin independent (in a free state) from the crosslinked structure (particularly the crosslinked gel structure) is the cause of the increase in the water-soluble matter, and thus the decrease in the water absorption properties (particularly the water absorption capacity under pressure) of the water absorbent resin, which is the final product. Furthermore, as a result of extensive research into means for reducing the water-soluble content, it has been found that the water-soluble content in the water-absorbent resin can be reduced by chemically incorporating a decomposition product of the water-absorbent resin into a crosslinked structure (particularly a crosslinked gel structure) and bonding the decomposition product of the water-absorbent resin to a part of the crosslinked structure of the crosslinked structure.
[0014] It should be noted that the above mechanism is merely speculation and does not limit the technical scope of the present invention.
[0015] Preferred embodiments of the present invention will be described below. Note that the present invention is not limited to the following embodiments, and can be modified in various ways within the scope of the claims. In addition, the embodiments described in this specification can be combined in any manner to form other embodiments.
[0016] In this specification, the term "(meth)acrylic" includes both acrylic and methacrylic. Thus, for example, the term "(meth)acrylic acid" includes both acrylic acid and methacrylic acid. Also, "acid (salt)" means "acid and / or its salt."
[0017] [1] Definitions of terms [1-1] Water-absorbing resin The "water-absorbent resin" produced by the method of the present invention is a water-swellable, water-insoluble polymer gelling agent, and refers to a conventional water-absorbent resin having a water-absorption capacity of 10 to 1000 times, although it is not particularly limited thereto. More specifically, the water-absorbent resin before absorbing the liquid to be absorbed preferably satisfies the physical property of CRC of 5 g / g or more as "water-swellability". The definition of CRC will be described later.
[0018] The water-absorbing resin may be a polymer derived from a carboxyl group-containing unsaturated monomer. The water-absorbing resin may include a polymer having a partially neutralized carboxyl group. Specific examples of the water-absorbing resin include polyacrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, cellulose-based resins, (meth)acrylate crosslinked polymers, saponified crosslinked products of (meth)acrylate-vinyl acetate copolymers, starch-acrylate graft polymers and crosslinked products thereof.
[0019] In this specification, the water-absorbing resin is not limited to an embodiment in which the total amount (100 mass %) is the water-absorbing resin alone, but may be a water-absorbing resin composition containing additives and the like.
[0020] [1-2] Recycled water-absorbent resin The term "recovered water-absorbent resin" refers to water-absorbent resin that should be discarded. Specifically, there are water-absorbent resins contained in used absorbent articles (for example, water-absorbent resins that have absorbed body fluids such as urine and blood in used absorbent articles) and water-absorbent resins discarded during the water-absorbent resin manufacturing process (for example, fine powder or non-standard water-absorbent resins generated during the water-absorbent resin manufacturing process).
[0021] Among these, it is preferable to use a water-absorbent resin recovered (removed and collected) from used absorbent articles from the viewpoint of environmental protection, etc. That is, in one embodiment of the present invention, the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article.
[0022] Here, "used absorbent articles" refer to sanitary materials that have been used by consumers and have absorbed bodily fluids such as urine and blood. Examples of sanitary materials include paper diapers, sanitary napkins, and adult incontinence products (incontinence pads). Products similar to sanitary materials include pet sheets and pet diapers, and in the present invention, these animal urine treatment products are also included in the sanitary materials.
[0023] The recovered water-absorbent resin is not limited to an embodiment in which the total amount (100% by mass) is the water-absorbent resin alone, and may be a water-absorbent resin composition containing a fibrous substance, a nonwoven fabric, an adhesive, an additive, etc. In addition, when the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article, the recovered water-absorbent resin may be in a state of a hydrous gel in which water such as urine water has been taken in. Therefore, the water-absorbent resin may contain a water-absorbent resin in a state of a hydrous gel.
[0024] The mass of the absorbent resin and the recovered absorbent resin is a value converted into solid content unless otherwise specified. For example, when the mass of the absorbent resin contained in the used paper diaper is unknown, the mass of the absorbent resin contained in the unused paper diaper and the general value of the water absorption ratio of the absorbent resin in the used paper diaper are used for calculation, or the content of the absorbent resin (solid content equivalent value) relative to the total mass of the used paper diaper is assumed to be 3% by mass or more and 9% by mass or less, and the mass of the absorbent resin is measured. Although the actual content of the absorbent resin may vary greatly depending on the usage state of the used paper diaper, a person skilled in the art can adjust the decomposition conditions appropriately while checking the actual decomposition state.
[0025] In one embodiment of the present invention, the CRC (before moisture absorption) of the recovered water absorbent resin (which is the raw material of the decomposition product) is 20 g / g or more, 25 g / g or more, 27 g / g or more, or 30 g / g or more. In one embodiment of the present invention, the CRC (before moisture absorption) of the recovered water absorbent resin (which is the raw material of the decomposition product) is 70 g / g or less, 50 g / g or less, or 45 g / g or less. The definition of CRC is as described in [1-5-1] below.
[0026] In one embodiment of the present invention, the AAP (0.3 psi) of the recovered water absorbent resin (the raw material of the decomposition product) is 10 g / g or more, 15 g / g or more, 20 g / g or more, 22 g / g or more, 24 g / g or more, or 25 g / g or more. In one embodiment of the present invention, the AAP (0.3 psi) of the water absorbent resin (the raw material of the decomposition product) is 50 g / g or less, 45 g / g or less, 40 g / g or less, 35 g / g or less, or 30 g / g or less. The definition of AAP is as described in [1-5-3] below.
[0027] [1-3] Absorbent articles An "absorbent article" is an article used for absorbing water. More specifically, an "absorbent article" is an absorbent article comprising an absorbent body containing a water-absorbent resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is suitably manufactured by blending a water-absorbent resin with a fibrous material, or by sandwiching a water-absorbent resin between fibrous materials and molding the mixture into a film, a tube, a sheet, or the like. Examples of the fibrous material include hydrophilic fibers such as ground wood pulp, cotton linters, crosslinked cellulose fibers, rayon, cotton, wool, acetate, vinylon, and the like.
[0028] The term "absorbent article" includes both unused absorbent articles and used absorbent articles. Here, "used absorbent articles" particularly include used sanitary materials that have absorbed body fluids (absorbed liquids) such as urine and blood. Examples of the sanitary materials include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets.
[0029] [1-4] Decomposition products The "decomposition product" is a product obtained by decomposing a water-swellable (i.e., insoluble in water) recovered water-absorbent resin, and can be solubilized in water. The decomposition product may be a product that is entirely solubilized in water, or a product that is partially solubilized. If the product appears dissolved in water with no residual residue visible in the water (if the interface between the water-absorbent resin and water cannot be visually recognized in the water), it is deemed to be solubilized in water. If some undissolved swollen matter remains but is reduced compared to before the solubilization treatment, it is deemed to be partially solubilized and a decomposition product is generated. Therefore, even if some undissolved swollen matter remains in the aqueous decomposition product solution after decomposition (solubilization), it is referred to as an aqueous decomposition product solution (or a dispersion of decomposition product). The obtained decomposition product may be used as it is in the form of an aqueous solution. Alternatively, the obtained decomposition product may be used in a solid state after drying to make it into a solid.
[0030] In one embodiment of the present invention, the mass average molecular weight of the decomposition product is 30,000 or more and 1,000,000 or less, or 40,000 or more and 800,000 or less. If the mass average molecular weight is within the above range, the amount of water-soluble content of the water-absorbent resin produced by using the decomposition product as a part of the raw material can be further reduced, and the water absorption properties can be further improved. In addition, the viscosity of the decomposition product solution (e.g., aqueous solution) can be appropriately controlled, so that the handling property is excellent. The definition of the mass average molecular weight is as described in [1-5-4] below.
[0031] [1-5] EDANA, WSP, and NWSP "EDANA" is an abbreviation for European Disposables and Nonwovens Associations, and "WSP" is an abbreviation for World Strategic Partners. EDANA WSP is a European and American standard (almost a global standard) for measuring the physical properties of water-absorbent resins. In the present invention, unless otherwise specified, the physical properties of the water-absorbent resin are measured in accordance with the original EDANA WSP (revised in 2010 / publicly known document).
[0032] "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015."
[0033] [1-5-1] CRC In this specification, the absorbency without load (CRC) is a value measured according to the following method.
[0034] (Measurement of Absorption Capacity under No Load (CRC)) "CRC" of a water-absorbent resin is an abbreviation for "Centrifuge Retention Capacity," and indicates the absorption capacity (unit: g / g) of a water-absorbent resin for 30 minutes under no pressure in a 0.90 mass % sodium chloride aqueous solution.
[0035] 0.200 g of water-absorbent resin is evenly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Industrial Co., Ltd., product name: Heatlon Paper, model: GSP-22), heat-sealed, and then immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag is pulled out and drained for 3 minutes using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122) at a centrifugal force (250 G) described in edana ABSORBENCY II 441.1-99, and the mass W1 (g) of the bag is measured. In addition, the same operation is performed without using the water-absorbent resin, and the mass W0 (g) at that time is measured. Then, from these W1 and W0, the CRC (centrifuge retention capacity) is calculated according to the following formula (1).
[0036]
number
[0037] [1-5-2] Water soluble matter (16-hour value) In this specification, the water-soluble content (16-hour value) is a value measured according to the following method. In this specification, the "water-soluble content (16-hour value)" is also referred to simply as "water-soluble content" or "water-soluble content" or "soluble polymer content".
[0038] (Measurement of water soluble matter (16-hour value)) 184.3 g of 0.90% by weight sodium chloride solution was weighed out into a 250 ml plastic container with a lid, 1.00 g of water-absorbent resin was added to the solution, and the mixture was stirred for 16 hours to extract the water-soluble components in the resin. The extract was filtered using a sheet of filter paper (Advantec Toyo Co., Ltd., product name: (JIS P 3801, No. 2), thickness 0.26 mm, retention particle size 5 μm), and 50.0 g of the filtrate was used as the measurement liquid.
[0039] Next, the measurement solution is titrated with a 0.1N-NaOH aqueous solution until the pH becomes 10, and then titrated with a 0.1N-HCl aqueous solution until the pH becomes 2.7. The titration amounts at this time are calculated as [NaOH] ml and [HCl] ml, respectively.
[0040] In addition, the same procedure is carried out using only 184.3 g of a 0.90% by mass aqueous sodium chloride solution without adding any water-absorbent resin, and the blank titration amount ([bNaOH] ml, [bHCl] ml) is determined.
[0041] When the water absorbent resin is composed of a known amount of acrylic acid and a salt thereof, the water-soluble content (unit: mass%) in the water absorbent resin can be calculated by the following formula (2) based on the average molecular weight of the monomer and the titration amount obtained by the above operation.
[0042]
number
[0043] [1-5-3] AAP0.3 (absorption rate under pressure) The "AAP" of the water absorbent resin of the present invention is an abbreviation for "Absorption Against Pressure" and indicates the absorbency against pressure (unit: g / g) for a 0.90 mass% sodium chloride aqueous solution. In this specification, unless otherwise specified, "AAP0.3", "absorption against pressure", and "AAP" are treated as synonyms.
[0044] AAP0.3 is measured in accordance with NWSP 242.0.R2(15) except that the pressure condition is changed from 0.7 psi to 0.3 psi. Specifically, a large excess of 0.9% by mass sodium chloride aqueous solution is used, and 0.9 g of the water-absorbent resin is subjected to pressure of 2.07 kPa (21 g / cm) for 1 hour. 2 After swelling under a pressure of 0.3 psi (0.02 psi), the AAP (absorbency under pressure) is measured. "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015."
[0045] [1-5-4] Molecular weight of water-absorbent resin and its decomposition products The molecular weight of the water-absorbent resin and its decomposition products are measured according to the following procedure.
[0046] (Preparation of measurement samples) The sample is dissolved in the following solvent to obtain a solution with a concentration of 0.1% by mass. The resulting solution is then passed through a filter (GL Sciences: GL Chromatodisk, aqueous 25A, pore size 0.2 μm) to obtain the measurement sample. Solvent: Aqueous solution (pH 6.35 to 6.38) containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM disodium hydrogen phosphate dodecahydrate, and 400 ppm sodium azide. Using this measurement sample, perform GPC measurement under the following measurement conditions.
[0047] (GPC measurement conditions) The sample was subjected to GPC measurement using Viscotec TDAmax manufactured by Malvern Instruments. The measurement device is equipped with a size exclusion chromatograph, a refractive index detector, a light scattering detector and a capillary viscometer. The measurement device and measurement conditions are as follows. Pump and autosampler: Viscotec GPCmax (Malvern Instruments) Guard column: OHpak SB-G (Showa Denko Co., Ltd.) Column: Two OHpak SB-806MHQ (Showa Denko K.K.) columns connected in series Detector: Viscotec TDAmax (Malvern) Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35 to 6.38). Flow rate: 0.5mL / min Injection volume: 100μL.
[0048] The water used in GPC measurement should be pure water from which impurities have been thoroughly removed. In addition, GPC measurement should be performed with a sufficient amount of solvent flowing through the measurement device, with the baseline of the detection value stable, and in particular, with no noise peaks in the light scattering detector.
[0049] The measurement device is calibrated using polyoxyethylene glycol [mass average molecular weight (Mw): 21966, molecular weight distribution (Mw / Mn): 1.0, differential refractive index (dn / dc): 0.132, solvent refractive index: 1.33] as a standard sample. The measurement is performed with the differential refractive index (dn / dc) of the decomposition product to be measured set to 0.12 and the solvent refractive index set to 1.33. Data collection and analysis of the refractive index, light scattering intensity, and viscosity are performed using Viscotek OmniSEC4.7.0 (registered trademark) software.
[0050] After the measurement, the data obtained from the refractive index (RI) and light scattering intensity (angle: 7°) (LALS), as well as the viscometer (DP) are used to calculate the mass average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) of the decomposition products.
[0051] [2] Method for producing a water-absorbing resin according to one embodiment of the first aspect In one embodiment of the present invention, the method for producing a water-absorbent resin of the present invention comprises producing a water-absorbent resin using a water-absorbent resin decomposition product obtained by decomposing a recovered water-absorbent resin as a part of a raw material, and the water-absorbent resin decomposition product is incorporated by a chemical method into a water-absorbent resin crosslinked structure obtained by polymerizing a monomer constituting the water-absorbent resin as a raw material. Here, the water-absorbent resin crosslinked structure is preferably composed of the monomer constituting the water-absorbent resin, and is preferably in a gel form (i.e., a water-absorbent resin crosslinked gel structure).
[0052] [2-1] Step of preparing water-absorbent resin decomposition product The recovered water-absorbent resin is decomposed to prepare a water-absorbent resin decomposition product. Here, the water-absorbent resin decomposition product may be produced by decomposing the recovered water-absorbent resin, may be a product obtained by commissioning another company to decompose the recovered water-absorbent resin, or may be a purchased water-absorbent resin decomposition product.
[0053] The method for producing the water absorbent resin decomposition product (decomposition product) is not particularly limited, and a known method can be used. For example, a technique for solubilizing the water absorbent resin by heating a mixture of the water absorbent resin and pulp in the presence of an oxidizing agent such as hydrogen peroxide or persulfate (e.g., JP-A-4-317785, JP-A-6-313008, JP-A-2003-321574), a technique for solubilizing the water absorbent resin using ascorbic acid as a reducing agent under conditions of pH 4 to pH 7.5 (e.g., JP-A-05-247221), a technique for solubilizing the water absorbent resin using a reducing agent and a transition metal ion (e.g., JP-A-2019-131789), and a technique for solubilizing the water absorbent resin by heating in the presence of an oxidizing water-soluble salt (e.g., WO2021 / 04211). 3), as a technique for decomposing a superabsorbent resin and solubilizing it in water, for example, a technique for solubilizing a water-absorbent resin using ozone water (e.g., JP 2014-217835 A, JP 2017-100133 A), a technique for solubilizing a water-absorbent resin using a combination of an oxidizing agent and a transition metal ion such as an iron ion or a copper ion (e.g., JP 11-172039 A), a technique for oxidation treatment with hypochlorous acid (salt), hydrogen peroxide, persulfuric acid, chlorine or a water-soluble oxidizing and reducing agent (e.g., JP 2013-150977 A), and a technique for solubilizing a water-absorbent resin using an alkali compound (e.g., JP 2020-49398 A) can be used.
[0054] An embodiment for producing a decomposition product will be described below, but the present invention is not limited to the following.
[0055] The recovered water absorbent resin, water and a decomposition agent are mixed. Here, the water is not particularly limited as long as it is clean, and examples thereof include tap water, industrial water, ion-exchanged water and pure water. The mixing ratio of water and recovered water absorbent resin (solid content) is not particularly limited, but the mixing amount of water is preferably 66 parts by mass or more and 9900 parts by mass or less, more preferably 80 parts by mass or more and 3200 parts by mass or less, and even more preferably 100 parts by mass or more and 1900 parts by mass or less, relative to 100 parts by mass of recovered water absorbent resin (solid content). If it is within the above range, it can be used as it is or after being concentrated in the subsequent manufacturing process. When the recovered water absorbent resin is in the state of a hydrous gel, the moisture absorbed in the water absorbent resin may be used as it is.
[0056] When preparing (manufacturing) a decomposition product from recovered water-absorbent resin contained in used absorbent articles, it is preferable to wash the used absorbent articles and recovered water-absorbent resin in advance to remove human waste and the like, and then perform the decomposition operation.
[0057] The decomposing agent is not particularly limited as long as it can decompose the recovered water absorbent resin and solubilize it in water, and may be any decomposing agent. Examples of the decomposing agent include an oxidizing agent, ozone water, a combination (mixture) of an oxidizing agent and a reducing agent, a combination (mixture) of an oxidizing agent and a transition metal ion such as iron ion or copper ion, a combination (mixture) of a reducing agent and a transition metal ion, and an alkali compound. When a decomposing agent (e.g., an oxidizing agent, an iron ion, an alkali compound, etc.) is contained in the recovered water absorbent resin, these decomposing agents may be used as they are.
[0058] An oxidizing agent may be used as the decomposition agent. The oxidizing agent is a compound having oxidizing properties and generates radicals by heating. Radicals are also generated by using an oxidizing agent in combination with a reducing agent and / or a compound that generates transition metal ions. Examples of the oxidizing agent include persulfates, such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides, such as hydrogen peroxide, alkyl hydroperoxides, and peroxide esters; perchlorates, such as sodium perchlorate and potassium perchlorate; periodates, such as sodium periodate and potassium periodate; percarbonates, perborates, and peracetic acid. The oxidizing agent may be used alone or in combination of two or more. Of these, hydrogen peroxide is preferably used. In this embodiment, the amount of the oxidizing agent is preferably 0.1 parts by mass or more and 50 parts by mass or less, more preferably 0.3 parts by mass or more and 30 parts by mass or less, and even more preferably 0.5 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin. When the amount of the oxidizing agent is within the above range, the recovered water absorbent resin can be efficiently decomposed, and coloration of the resulting decomposition product can be sufficiently prevented.
[0059] A reducing agent may be used as the decomposing agent. The reducing agent is a compound having reducing properties, and generates radicals when used in combination with the above-mentioned oxidizing agent or the below-mentioned compound that generates transition metal ions. Examples of the reducing agent include sulfurous acid (salt), hydrogen sulfite (salt), phosphorous acid (salt), hypophosphorous acid (salt), thiosulfuric acid (salt), formic acid, oxalic acid, erythorbic acid, amines, ascorbic acid (salt) or its derivatives (e.g., L-ascorbic acid (salt), isoascorbic acid (salt), and alkyl esters of ascorbic acid), phosphoric acid esters, and sulfate esters. The reducing agent may be used alone or in combination of two or more kinds. Among these, sulfurous acid (salt), hydrogen sulfite (salt), L-ascorbic acid (salt), and isoascorbic acid (salt) are preferably used. In this embodiment, the amount of the reducing agent is preferably 0.01 parts by mass or more and 50 parts by mass or less, more preferably 0.05 parts by mass or more and 25 parts by mass or less, and even more preferably 0.1 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin. With this amount of the reducing agent, the recovered water absorbent resin can be efficiently decomposed, and coloring of the resulting decomposition product can be sufficiently prevented.
[0060] A transition metal ion may be used as the decomposition agent. The transition metal ion generates radicals by the Fenton reaction when used in combination with the above-mentioned oxidizing agent. Also, the transition metal ion generates radicals when used in combination with the above-mentioned reducing agent. Examples of the transition metal ion include Cu. 2+ , Ag + , Fe 2+ , Fe 3+ , Al 3+ , Ni 2+ , Mn 2+ The transition metal ions may be used alone or in combination of two or more. Among these, iron ion (Fe 2+ ), copper ions (Cu 2+ ) is preferred, and iron ions (Fe 2+) is more preferable. Examples of the compound that generates the transition metal ions as described above include chlorides and hydrates thereof, such as ferrous chloride, organic acid salts and hydrates thereof, such as ferrous fumarate, ferrous oxalate, ferrous chloride, sodium ferrous citrate, ferrous gluconate, ferrous citrate, ferrous acetate, sulfates and hydrates thereof, such as ferrous sulfate, and the like. The compounds may be used alone or in combination of two or more. In this embodiment, the amount of transition metal ions is 1×10 to 100 parts by mass of the recovered water absorbent resin. -6 It is preferably from 1 part by mass to 1 part by mass, and more preferably from 1×10 -5 The amount of the transition metal ion is preferably from 0.001 to 0.1 parts by mass, more preferably from 0.02 to 0.5 parts by mass, and even more preferably from 0.001 to 0.1 parts by mass. The amount of the transition metal ion is such that the recovered water absorbent resin can be efficiently decomposed and coloration of the resulting decomposition product can be sufficiently prevented.
[0061] An alkaline compound may be used as the decomposing agent. The alkaline compound is a compound that solubilizes the crosslinked portion of the water-absorbent resin by alkaline hydrolysis. Examples of such alkaline compounds include hydroxides of alkali metals such as lithium hydroxide, potassium hydroxide, and sodium hydroxide; hydroxides of alkaline earth metals such as magnesium hydroxide and calcium hydroxide; ammonia; and amine compounds such as aliphatic amines, alicyclic amines, and aromatic amines. The alkaline compounds may be used alone or in combination of two or more kinds. Among these, hydroxides of alkali metals and hydroxides of alkaline earth metals are preferred.
[0062] In one embodiment of the present invention, the decomposition agent comprises at least two selected from an oxidizing agent, a reducing agent, and a transition metal ion. In one embodiment of the present invention, the decomposition agent comprises an oxidizing agent, a reducing agent, and a transition metal ion. In one embodiment of the present invention, the decomposition agent comprises at least two selected from a peroxide, an ascorbic acid (salt) or a derivative thereof, and a transition metal ion. In one embodiment of the present invention, the decomposition agent comprises a peroxide, an ascorbic acid (salt) or a derivative thereof, and a transition metal ion.
[0063] The decomposition conditions are not particularly limited, but it is preferable to carry out the decomposition under appropriate pH conditions. Specifically, it is preferable to adjust the pH of the mixture containing the recovered water absorbent resin, water, and the decomposition agent to a range of 6.5 to 8.5 (more preferably 6.5 to 8.3, particularly preferably 6.5 to 8.0). If the pH is within the above range, the recovered water absorbent resin can be efficiently decomposed, and coloring of the resulting decomposition product can be sufficiently prevented. The pH of the mixture may be adjusted within the range for a certain period of time that allows the decomposition of the recovered water absorbent resin to proceed sufficiently. It is preferable to adjust the pH to fall within the above pH range from the start of decomposition to the end of decomposition. The pH of the mixture can be adjusted by adding a pH adjuster such as an acid or a base as necessary. Examples of acids to be used include, but are not limited to, inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid and citric acid. Examples of bases that can be used include, but are not limited to, sodium hydroxide, sodium carbonate, potassium hydroxide hydroxide, and magnesium hydroxide.
[0064] The temperature at which the recovered water-absorbent resin is decomposed is preferably 50°C or higher and 130°C or lower, more preferably 65°C or higher and 120°C or lower, and even more preferably 80°C or higher and 110°C or lower. At the above temperature, a sufficient amount of radicals is generated from the decomposing agent, and the decomposed product can be obtained in a short time. As a method for adjusting the decomposition temperature, the recovered water-absorbent resin, the decomposing agent, and water may be mixed at room temperature (for example, 20°C or higher and 25°C or lower), and then the temperature of the mixture may be adjusted to a predetermined value while stirring if necessary. Alternatively, the recovered water-absorbent resin, the decomposing agent, and water may be introduced into a container whose temperature has been adjusted to a predetermined temperature by a known means such as a jacket, and then stirred.
[0065] By the decomposition operation, a decomposition product (water-absorbent resin decomposition product) is obtained.
[0066] [2-2] A process for producing a water-absorbent resin using a decomposed product of the water-absorbent resin as part of the raw material In the method for producing a water absorbent resin according to the present invention, the decomposition product prepared in the above [2-1] is used as a part of the raw material, and the decomposition product is incorporated by a chemical method into a water absorbent resin crosslinked structure (particularly a water absorbent resin crosslinked gel structure) obtained by polymerizing a monomer constituting the water absorbent resin, which is the final product, as a raw material.
[0067] In this specification, "incorporating a decomposition product of a water-absorbent resin into a crosslinked water-absorbent resin structure obtained by polymerizing a monomer constituting a water-absorbent resin as a raw material" means that the decomposition product of the water-absorbent resin is chemically bonded to the crosslinked structure of the crosslinked water-absorbent resin structure at one or more sites in the molecule. Therefore, according to the method of the present invention, the decomposition product does not come off the crosslinked structure even under load conditions such as swelling or under pressure, and therefore the water-soluble content (soluble polymer amount) can be significantly reduced.
[0068] Here, the chemical method is preferably carried out before the surface cross-linking step. By carrying out the chemical method before the surface cross-linking step, the decomposition products can be incorporated not only on the surface of the cross-linked structure but also inside. Therefore, the amount of soluble polymer can be further reduced (hence, the decrease in the water absorption performance (particularly the water absorption capacity under pressure) of the obtained water absorbent resin can be more effectively suppressed). On the other hand, when the chemical method is carried out during or after the surface cross-linking step, the decomposition products are preferentially incorporated into the surface of the cross-linked structure. Therefore, the decomposition products are not incorporated in a sufficient amount inside the cross-linked structure. Therefore, there is a possibility that the water-soluble content is not sufficiently reduced (hence, the decrease in the water absorption performance (particularly the water absorption capacity under pressure) of the obtained water absorbent resin cannot be sufficiently suppressed).
[0069] That is, in a preferred embodiment of the present invention, the method according to the present invention further comprises a surface cross-linking step, and the chemical technique is carried out prior to the surface cross-linking step.
[0070] In one embodiment of the present invention, the process for producing the water-absorbent resin preferably includes a monomer aqueous solution preparation step, a polymerization step, a hydrogel crushing step, and a drying step.
[0071] In the case where the chemical method is carried out before the surface cross-linking step, the chemical method is preferably carried out in any one of the steps of the monomer aqueous solution preparation step, the polymerization step, the hydrogel crushing step and the drying step, and more preferably in the monomer aqueous solution preparation step or the polymerization step. It is more preferable that the decomposition product is incorporated into the cross-linked structure in the polymerization step. This allows the decomposition product to be more efficiently incorporated into the entire cross-linked structure (both the surface layer and the inside).
[0072] Hereinafter, an embodiment in which a chemical method is implemented in a polymerization process will be described, but the present invention is not limited to the following embodiment, and the chemical method described in detail below can be applied to other processes in the same manner or with appropriate modifications.
[0073] [2-2-1] Monomer aqueous solution preparation process This step is a step of preparing an aqueous solution containing a carboxyl group-containing unsaturated monomer, particularly acrylic acid (salt), as a main component (hereinafter referred to as "aqueous monomer solution"). Although a monomer slurry liquid can be used within a range in which the water absorption performance of the resulting water absorbent resin is not reduced, for the sake of convenience, the aqueous monomer solution will be described in this section.
[0074] The "main component" means that the amount (content) of the carboxyl group-containing unsaturated monomer (particularly, acrylic acid (salt)) used is usually 50 mol % or more, preferably 70 mol % or more, and more preferably 90 mol % or more (upper limit: 100 mol %) relative to the monomers (excluding an internal crosslinking agent and an external crosslinking agent, if used; the same applies below) subjected to the polymerization reaction of the water absorbent resin.
[0075] As the solvent for the aqueous monomer solution, water or a mixture of water and a water-soluble organic solvent (e.g., alcohol, etc.) is preferably used, and water is even more preferred. In the case of a mixture of water and a water-soluble organic solvent, the content of the water-soluble organic solvent (e.g., alcohol, etc.) is preferably 30% by mass or less, and more preferably 5% by mass or less, when the total mass of the solvent is taken as 100% by mass.
[0076] In the following, a case where the monomer is acrylic acid (salt) will be described, but the present invention is not limited to the following.
[0077] (acrylic acid) In one embodiment of the present invention, from the viewpoint of the physical properties and productivity of the obtained water absorbent resin, acrylic acid and / or a salt thereof (hereinafter, referred to as "acrylic acid (salt)") is used as a monomer constituting the water absorbent resin.
[0078] The "acrylic acid" may be a known acrylic acid, and may contain a polymerization inhibitor, preferably 200 ppm or less, more preferably 10 ppm or more and 160 ppm or less, and even more preferably 20 ppm or more and 100 ppm or less, from the viewpoint of the polymerizability of acrylic acid and the color tone of the water-absorbing resin. The polymerization inhibitor is preferably a methoxyphenol, more preferably p-methoxyphenol. In addition, as for impurities in acrylic acid, the compounds described in U.S. Patent Application Publication No. 2008 / 0161512 are also applicable to one embodiment of the present invention.
[0079] The "acrylate" is obtained by neutralizing the acrylic acid with the following basic composition. The acrylate may be a commercially available acrylate (e.g., sodium acrylate) or may be one obtained by neutralization in a water-absorbent resin manufacturing plant.
[0080] (Basic Composition) In one embodiment of the present invention, the term "basic composition" refers to a composition containing a basic compound, such as a commercially available aqueous sodium hydroxide solution.
[0081] Specific examples of the basic compound include carbonates and / or hydrogen carbonates of alkali metals, hydroxides of alkali metals, ammonia, organic amines, and the like. Among these, from the viewpoint of the physical properties of the obtained water absorbent resin, it is desirable to use a strong basic compound. That is, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred, and sodium hydroxide is more preferred. That is, the salt of acrylic acid is preferably at least one selected from alkali metal salts, ammonium salts, and amine salts of acrylic acid, more preferably an alkali metal salt of acrylic acid, even more preferably at least one selected from sodium salts, lithium salts, and potassium salts of acrylic acid, and particularly preferably a sodium salt of acrylic acid.
[0082] (neutralization) As the neutralization in one embodiment of the present invention, either neutralization of acrylic acid (before polymerization) or neutralization of a hydrogel-like crosslinked polymer obtained by crosslinking and polymerizing acrylic acid (after polymerization) (hereinafter referred to as "post-neutralization") can be selected or used in combination. When the decomposition product is used as at least a part of the raw material in the production of a water-absorbent resin, if the decomposition product contains a basic compound, this basic compound neutralizes the acrylic acid before polymerization or the hydrogel-like crosslinked polymer after polymerization. Therefore, the neutralization rate of the water-absorbent resin as the final product may be adjusted to a predetermined range by adding this basic compound. Regarding the conditions such as the apparatus for performing neutralization, the neutralization temperature, and the residence time, the conditions described in International Publication No. 2009 / 123197 and US Patent Application Publication No. 2008 / 0194863 may also be applied to the present invention. The neutralization in one embodiment of the present invention may be performed by adding a basic compound to the aqueous monomer solution in multiple stages. In addition, the neutralization in one embodiment of the present invention may be performed in a continuous or batch manner.
[0083] In one embodiment of the present invention, the neutralization rate is preferably 10 mol% to 90 mol%, more preferably 40 mol% to 85 mol%, even more preferably 50 mol% to 80 mol%, and particularly preferably 60 mol% to 75 mol% based on the acid group of the monomer. With such a neutralization rate, a water-absorbing resin with high water absorption properties (particularly water absorption capacity under pressure) can be obtained. For example, a neutralization rate of 75 mol% means a mixture of 25 mol% acrylic acid and 75 mol% acrylic acid salt. This may also be called a partially neutralized product of acrylic acid.
[0084] The neutralization rate is the same in the case of post-neutralization. The neutralization rate is also applied to the neutralization rate of the water-absorbent resin as a final product. The present invention is characterized in that the recycled water-absorbent resin is used as a part of the raw material in the production of the water-absorbent resin. When the recycled water-absorbent resin contains the basic compound, the neutralization of the acrylic acid (before polymerization) and / or the post-neutralization of the hydrogel-like crosslinked polymer is appropriately adjusted so that the neutralization rate of the water-absorbent resin as a final product, including the basic compound, falls within a predetermined range.
[0085] (Water absorbent resin decomposition product) The water absorbent resin decomposition product (decomposition product) may be added in the following polymerization step, which is the next step, or the monomer aqueous solution may contain the decomposition product. In the latter case, the mixing ratio of the decomposition product and the crosslinked structure in the monomer aqueous solution is preferably such that the monomer aqueous solution contains the decomposition product at a ratio (solid content) of 1% by mass or more and 60% by mass or less with respect to the total mass of the monomer (e.g., acrylic acid) and the decomposition product when producing the water absorbent resin (the total mass is taken as 100% by mass). That is, in one embodiment of the present invention, the decomposition product is used at 1% by mass or more and 60% by mass or less with respect to the total mass (total mass of the water absorbent resin) of the monomer (e.g., acrylic acid) and the decomposition product when producing the water absorbent resin. It is more preferable that the monomer aqueous solution contains the decomposition product at a ratio of 3% by mass or more and less than 50% by mass with respect to the total mass of the monomer (e.g., acrylic acid) and the decomposition product when producing the water absorbent resin (the total mass is taken as 100% by mass) (i.e., the decomposition product is used at a ratio of 3% by mass or more and less than 50% by mass with respect to the total mass of the monomer (e.g., acrylic acid) and the decomposition product when producing the water absorbent resin (total mass of the water absorbent resin)). It is particularly preferable that the monomer aqueous solution contains the decomposition product at a ratio of more than 5% by mass and less than 40% by mass with respect to the total mass of the monomer (e.g., acrylic acid) and the decomposition product when producing the water absorbent resin (the total mass is taken as 100% by mass) (i.e., the decomposition product is used at a ratio of more than 5% by mass and less than 40% by mass with respect to the total mass of the monomer (e.g., acrylic acid) and the decomposition product when producing the water absorbent resin (total mass of the water absorbent resin)). With such a mixing ratio, the decomposition product can be more appropriately incorporated into the crosslinked structure (hence, the water-soluble content can be more effectively reduced).
[0086] (Other monomers) In one embodiment of the present invention, the term "other monomer" refers to a monomer other than the acrylic acid (salt), and the water-absorbing resin can be produced by using the other monomer together with the acrylic acid (salt).
[0087] The other monomer may be a water-soluble or hydrophobic unsaturated monomer. Specifically, the compounds described in U.S. Patent Application Publication No. 2005 / 0215734 (excluding acrylic acid) are also applicable to one embodiment of the present invention.
[0088] (Polymerization initiator) A polymerization initiator can be used in the preparation of the monomer aqueous solution, if necessary. The polymerization initiator is not particularly limited, since it is appropriately selected depending on the polymerization form, etc. For example, a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a redox-based polymerization initiator in combination with a reducing agent that promotes the decomposition of these polymerization initiators can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 are used. In addition, from the viewpoint of the handling of the polymerization initiator, the physical properties of the water-absorbing resin, etc., preferably a peroxide or an azo compound, more preferably a peroxide, even more preferably a persulfate such as sodium persulfate, potassium persulfate, or ammonium persulfate, and particularly preferably sodium persulfate is used.
[0089] The amount of the polymerization initiator used is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.005 mol% or more and 0.5 mol% or less, and even more preferably 0.01 mol% or more and 0.3 mol% or less, based on the monomers used in the polymerization reaction of the water absorbent resin. The amount of the reducing agent used is preferably 0.0001 mol% or more and 0.02 mol% or less, based on the monomers. The mol% based on the monomers refers to the percentage of the number of moles of the polymerization initiator or the reducing agent based on the total number of moles of the monomers contained in the aqueous monomer solution (excluding the internal crosslinking agent and the external crosslinking agent, if used).
[0090] If necessary, the photodecomposition type polymerization initiator may be used in combination with other polymerization initiators such as a photodecomposition type polymerization initiator. Specific examples of the photodecomposition type polymerization initiator include benzoin derivatives, benzyl derivatives, acetophenone derivatives, and benzophenone derivatives.
[0091] Instead of the polymerization initiator, the polymerization reaction may be carried out by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays, or these active energy rays may be used in combination with the polymerization initiator.
[0092] (Internal crosslinking agent) An internal crosslinking agent is used in the preparation of the monomer aqueous solution. The crosslinked structure may be composed of a monomer and an internal crosslinking agent. As the internal crosslinking agent, the compounds described in U.S. Pat. No. 6,241,928 are also applied to one embodiment of the present invention. Among these, one or more compounds are selected in consideration of reactivity.
[0093] From the viewpoint of the water absorption performance of the obtained water absorbent resin, a compound having two or more polymerizable unsaturated groups in one molecule is preferably used as the internal crosslinking agent. More preferably, a compound having thermal decomposition properties, and even more preferably, a compound having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structural unit, is used as the internal crosslinking agent.
[0094] The polymerizable unsaturated group is preferably an allyl group or a (meth)acrylate group, more preferably a (meth)acrylate group. The (poly)alkylene glycol structural unit is preferably polyethylene glycol, and the number n is preferably 1 or more and 100 or less, more preferably 6 or more and 50 or less.
[0095] Examples of such internal crosslinking agents include N,N'-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane di(meth)acrylate, glycerin tri(meth)acrylate, glycerin acrylate methacrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, triallylamine, poly(meth)allyloxyalkane, etc. These internal crosslinking agents may be used alone or in combination of two or more.
[0096] The amount of the internal crosslinking agent used is preferably 0.0001 mol% or more and 5 mol% or less, more preferably 0.001 mol% or more and 1.5 mol% or less, and particularly preferably 0.01 mol% or more and less than 1.0 mol% relative to the monomer (excluding the internal crosslinking agent and the external crosslinking agent, if used). By setting the amount used within the above range, a desired water-absorbing resin can be obtained. With such an amount used, it is possible to suppress a decrease in gel strength and an increase in water-soluble matter, and to achieve excellent water absorption properties. The mol% relative to the total monomer refers to the percentage of the number of moles of the internal crosslinking agent relative to the total number of moles of the monomer (excluding the internal crosslinking agent and the external crosslinking agent, if used) contained in the aqueous monomer solution.
[0097] In one embodiment of the present invention, a method is preferably applied in which a predetermined amount of an internal crosslinking agent is added to an aqueous monomer solution in advance, and a crosslinking reaction is carried out simultaneously with polymerization. On the other hand, other than the above method, a method of post-crosslinking by adding an internal crosslinking agent during and / or after polymerization, a radical crosslinking method using a radical polymerization initiator, a radiation crosslinking method using active energy rays such as electron beams and ultraviolet rays, etc. can also be adopted. These methods can also be used in combination.
[0098] (Other substances added to the monomer aqueous solution) In one embodiment of the present invention, from the viewpoint of improving the physical properties of the resulting water-absorbent resin, the following substances may be added during preparation of the aqueous monomer solution.
[0099] Specifically, hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts) can be added in amounts of preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (the lower limit is 0% by mass); foaming agents such as carbonates and azo compounds, surfactants, chelating agents, chain transfer agents, etc. can be added in amounts of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (the lower limit is 0% by mass); and the like.
[0100] In addition, the following substances (hereinafter referred to as "other substances") may be added to the aqueous monomer solution. Specific examples of other substances include chain transfer agents such as thiols, thiolic acids, secondary alcohols, amines, and hypophosphites; foaming agents such as carbonates, bicarbonates, azo compounds, and bubbles; chelating agents such as metal salts of ethylenediaminetetraacetic acid and metal salts of diethylenetriaminepentaacetic acid; thickeners such as polyacrylic acid (salts) and crosslinked products thereof, starch, cellulose, starch-cellulose derivatives, and polyvinyl alcohol. The other substances may be used alone or in combination of two or more.
[0101] The amount of the other substances used is not particularly limited, but the total concentration of the other substances is preferably from 0.0001% by mass to 10% by mass, more preferably from 0.0005% by mass to 1% by mass, and even more preferably from 0.001% by mass to 0.1% by mass, based on the monomer (excluding the internal crosslinking agent and the external crosslinking agent, if used) or (when the aqueous monomer solution contains the monomer and decomposition products) based on the total amount of the monomer and decomposition products (excluding the internal crosslinking agent and the external crosslinking agent, if used).
[0102] The above-mentioned substance and chelating agent may be added not only to the aqueous monomer solution but also during the polymerization, or these forms may be used in combination.
[0103] The dissolved oxygen in the aqueous monomer solution may be reduced by raising the temperature or by replacing the oxygen with an inert gas.
[0104] The concentration of the monomer in the aqueous monomer solution or (when the aqueous monomer solution contains a monomer and a decomposition product) the monomer and the decomposition product is selected according to the type of the selected monomer, the decomposition product, and the organic solvent, etc. In terms of production efficiency, the lower limit is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. The upper limit is preferably 100% by mass or less, more preferably 90% by mass or less, even more preferably 80% by mass or less, and even more preferably 70% by mass or less.
[0105] As long as the object of the present invention is not hindered, additives such as surfactants, density regulators, thickeners, etc. can be added to the aqueous monomer solution. The type and amount of the additives can be appropriately selected depending on the combination of the monomers and organic solvents used.
[0106] As described below, when the polymerization step is carried out by the method i) below, it is preferable that the aqueous monomer solution further contains a crosslinking agent capable of reacting with both the decomposition product and the crosslinked structure, and this form is the form in the method i) of the polymerization step described below in [2-2-2].
[0107] [2-2-2] Polymerization process In this step, the aqueous monomer solution prepared above is polymerized. As a result, the monomer is crosslinked by the internal crosslinking agent to obtain a water-absorbent resin crosslinked structure (particularly, a water-absorbent resin crosslinked gel structure). In addition, in this step, it is preferable to incorporate a water-absorbent resin decomposition product (decomposition product) into the water-absorbent resin crosslinked structure obtained here by a chemical method.
[0108] (polymerization form) The polymerization form applied to one embodiment of the present invention is not particularly limited, but from the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferably, spray droplet polymerization, aqueous solution polymerization, and reversed phase suspension polymerization, more preferably, aqueous solution polymerization, and reversed phase suspension polymerization, and further preferably, aqueous solution polymerization are mentioned. Among them, continuous aqueous solution polymerization is particularly preferable, and either continuous belt polymerization or continuous kneader polymerization is applicable.
[0109] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin is improved.
[0110] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization". "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination. For example, the polymerization temperature is preferably 20°C or higher and 100°C or lower, more preferably 40°C or higher and 90°C or lower.
[0111] In one embodiment of the present invention, the polymerization can be carried out under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, for example, it is preferable to control the oxygen concentration to 1 volume % or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, dissolved oxygen; less than 1 mg / l).
[0112] In one embodiment of the present invention, the polymerization may be carried out as foaming polymerization in which bubbles (particularly the inert gases or the like) are dispersed in an aqueous monomer solution to carry out the polymerization.
[0113] As described above, in a preferred embodiment, in this step, the decomposition product is incorporated into the crosslinked structure by a chemical method. In one embodiment of the present invention, the decomposition of the recovered water absorbent resin and the incorporation of the decomposition product into the crosslinked structure are performed in separate steps. Therefore, the structure and decomposition property of the decomposition product and the chemical incorporation can be controlled independently.
[0114] As described above, the decomposition product of the water absorbent resin (decomposition product) may be added in the main polymerization step. Specifically, the decomposition product may be added separately to the polymerization apparatus. In this case, as the mixing ratio of the decomposition product and the crosslinked structure, it is preferable to use 1% by mass or more and 60% by mass or less of the decomposition product with respect to the total mass of the water absorbent resin (total mass of the water absorbent resin is taken as 100% by mass). It is more preferable to use 3% by mass or more and less than 50% by mass with respect to the total mass of the water absorbent resin (total mass of the water absorbent resin is taken as 100% by mass). It is particularly preferable to use more than 5% by mass and less than 40% by mass with respect to the total mass of the water absorbent resin (total mass of the water absorbent resin is taken as 100% by mass). With such a mixing ratio, the decomposition product can be more appropriately incorporated into the crosslinked structure (hence, the water-soluble content can be more effectively reduced). In the above, the "total mass of the water absorbent resin" refers to the total mass of the monomer (e.g., acrylic acid) and the decomposition product when producing the water absorbent resin. When the aqueous monomer solution contains a predetermined amount of decomposition products, it is not necessary to add the decomposition products separately in the polymerization step.
[0115] Also, examples of methods for incorporating the decomposition product into a water-absorbent resin crosslinked structure (particularly a water-absorbent resin crosslinked gel structure) by a chemical method include the following methods i) to v). That is, the chemical method includes at least one method selected from the group consisting of the following methods i) to v).
[0116] i) adding a crosslinking agent capable of reacting with both the decomposition product of the water-absorbent resin and the crosslinked structure of the water-absorbent resin; ii) introducing a double bond into the decomposition product of the water absorbent resin; iii) adding a hydrogen abstraction type peroxide to the decomposition product of the water absorbent resin and the crosslinked structure of the water absorbent resin; iv) adding a photoinitiator and / or a photosensitizer to the water-absorbent resin decomposition product and the water-absorbent resin crosslinked structure; and v) Irradiating the decomposition product of the water-absorbent resin and the crosslinked structure of the water-absorbent resin with radiation.
[0117] [Method i] In this method, a crosslinking agent capable of reacting with both the decomposition product and the water-absorbent resin crosslinked structure (particularly the water-absorbent resin crosslinked gel structure) is added to incorporate the decomposition product into the crosslinked structure (particularly the crosslinked gel structure). Preferably, the polymerization step is carried out in the presence of a crosslinking agent capable of reacting with both the decomposition product and the crosslinked structure, and more preferably, in the monomer aqueous solution preparation step [2-2-1], an aqueous monomer solution containing a monomer, a decomposition product, and a crosslinking agent capable of reacting with both the decomposition product and the crosslinked structure is prepared, and the aqueous monomer solution is subjected to this polymerization step. In this specification, the crosslinking agent capable of reacting with both the decomposition product and the crosslinked structure is also simply referred to as an "external crosslinking agent".
[0118] Here, the external crosslinking agent has a reactive group in the molecule that can react with a carboxyl group or its salt present in the structural unit derived from acrylic acid (salt), and preferably has two or more reactive groups in one molecule, or has a reactive group and a polymerizable unsaturated group in one molecule. Here, examples of the reactive group include epoxy groups such as glycidyl groups, -NH groups, and hydroxyl groups. Specifically, examples of the external crosslinking agent include epoxy compounds such as (poly)ethylene glycol diglycidyl ether and glycerol diglycidyl ether, polyhydric alcohol compounds such as ethylene glycol, polyethylene glycol, propylene glycol, glycerin, 1,4-butanediol, and pentaerythritol, alkylene carbonate compounds such as ethylenediamine, ethylene carbonate, and propylene carbonate, and polyethyleneimine. These external crosslinking agents may be used alone or in combination.
[0119] Among these, since the decomposition products are easily and efficiently incorporated into the crosslinked polymer, the external crosslinking agent preferably contains at least one selected from the group consisting of epoxy compounds, polyhydric alcohol compounds, and alkylene carbonate compounds, more preferably an epoxy compound, even more preferably (poly)ethylene glycol diglycidyl ether, and particularly preferably ethylene glycol diglycidyl ether.
[0120] The polymerization step is preferably carried out in the presence of an internal crosslinking agent and an external crosslinking agent. In this case, the combination of the internal crosslinking agent and the external crosslinking agent is preferably a combination of (poly)ethylene glycol di(meth)acrylate and (poly)ethylene glycol diglycidyl ether, a combination of (poly)ethylene glycol di(meth)acrylate and ethylene carbonate, a combination of (poly)ethylene glycol di(meth)acrylate and propylene carbonate, a combination of (poly)ethylene glycol di(meth)acrylate, ethylene carbonate and propylene carbonate, a combination of (poly)ethylene glycol di(meth)acrylate and (poly)ethylene glycol diglycidyl ether is more preferable, and a combination of polyethylene glycol diacrylate and ethylene glycol diglycidyl ether is particularly preferable. With such a combination, the decomposition product is more efficiently and firmly incorporated into the crosslinked structure.
[0121] As a method for using the external crosslinking agent, a method is preferably applied in which the external crosslinking agent is added to the monomer aqueous solution in advance and chemically incorporated at the same time as polymerization. On the other hand, in addition to the above method, a method of adding the external crosslinking agent during and / or after polymerization and then performing surface crosslinking can also be adopted. These methods can also be used in combination.
[0122] The amount of the external crosslinking agent used is preferably 0.010 mol% or more and 1 mol% or less, more preferably 0.020 mol% or more and 0.750 mol% or less, particularly preferably more than 0.030 mol% and 0.500 mol% or less, based on the total monomer (excluding the internal crosslinking agent and the external crosslinking agent). By setting the amount used within the above range, the water-soluble content (soluble polymer amount) can be further reduced, and even if the water-absorbent resin is produced using a water-absorbent resin that should be discarded, the decrease in water-absorbency (particularly the water-absorbency capacity under pressure) can be more effectively suppressed (therefore, the water-absorbency capacity (particularly the water-absorbency capacity under pressure) of the water-absorbent resin obtained can be improved). The mol% relative to the total monomer is the percentage of the number of moles of the external crosslinking agent relative to the total number of moles of the monomer contained in the aqueous monomer solution. The amount of the external crosslinking agent used is substantially equal to the ratio of the amount charged.
[0123] [Method ii)] In this method, the water-absorbent resin decomposition product is incorporated into a water-absorbent resin crosslinked structure (particularly a water-absorbent resin crosslinked gel structure) by introducing a double bond into the water-absorbent resin decomposition product. Preferably, the decomposition product is incorporated into the crosslinked structure by carrying out a polymerization step in the presence of a compound having a reactive group and a polymerizable unsaturated group capable of reacting with a carboxyl group or its salt present in the structural unit derived from acrylic acid (salt). More preferably, a compound having a reactive group and a polymerizable unsaturated group capable of reacting with a carboxyl group or its salt present in acrylic acid (salt) is added to the decomposition product and the crosslinked structure during the polymerization step, or in the monomer aqueous solution preparation step [2-2-1], an aqueous monomer solution containing acrylic acid (salt), the decomposition product, and a compound having a reactive group and a polymerizable unsaturated group capable of reacting with a carboxyl group or its salt present in acrylic acid (salt) is prepared, and the aqueous monomer solution is subjected to the main polymerization step, thereby incorporating the decomposition product into the crosslinked structure. Particularly preferably, in the monomer aqueous solution preparation step [2-2-1], an aqueous monomer solution containing acrylic acid (salt), the decomposition product, and a compound having a reactive group capable of reacting with a carboxyl group or its salt present in the acrylic acid (salt) and a polymerizable unsaturated group is prepared, and the aqueous monomer solution is subjected to the main polymerization step, thereby incorporating the decomposition product into a crosslinked structure (particularly a crosslinked gel structure). In this specification, the compound having a reactive group capable of reacting with a carboxyl group or its salt present in the acrylic acid (salt) and a polymerizable unsaturated group is also referred to as a "double bond introducing agent".
[0124] Here, the double bond introducing agent is a compound having a reactive group and a polymerizable unsaturated group that can react with a carboxyl group or its salt present in acrylic acid (salt). Depending on the type of double bond introducing agent, the reactive group (e.g., epoxy group) and the type of double bond (e.g., (meth)acryloyl group) can be freely selected. Therefore, depending on the reactive group and the type of double bond, the introduction site into the crosslinked structure (especially the crosslinked gel structure) of the decomposition product can be adjusted.
[0125] The reactive group includes an epoxy group and an isocyanate group. Examples of the double bond introducing agent include compounds having both an epoxy group and a double bond, such as glycidyl (meth)acrylate and allyl glycidyl ether; compounds having both an isocyanate group and a double bond, such as 2-isocyanate ethyl (meth)acrylate and 1,1-(bisacryloyloxymethyl)ethyl isocyanate. These double bond introducing agents may be used alone or in combination of two or more.
[0126] A preferred method for using the double bond-introducing agent is to add the double bond-introducing agent to an aqueous monomer solution in advance and chemically incorporate the agent at the same time as polymerization. In addition to the above method, a method of adding the double bond-introducing agent during and / or after polymerization to perform post-crosslinking, etc., can also be used. These methods can also be used in combination.
[0127] The amount of the double bond introducing agent used is preferably 0.010% by mass or more and 10% by mass or less, more preferably 0.10% by mass or more and 5.0% by mass or less, based on the decomposition product. By setting the amount used within the above range, a desired water absorbent resin can be obtained. With the amount used, the water soluble content (soluble polymer amount) can be further reduced, and even if the water absorbent resin is produced using a water absorbent resin that should be discarded, the decrease in water absorption performance (particularly water absorption capacity under pressure) can be more effectively suppressed (therefore, the water absorption performance (particularly water absorption capacity under pressure) of the obtained water absorbent resin can be improved). The mass % based on the decomposition product is the percentage of the content (mass) of the double bond introducing agent to the content (mass) of the decomposition product contained in the monomer aqueous solution.
[0128] [iii) Method] In this method, a hydrogen abstraction type peroxide is added to a water absorbent resin decomposition product and a water absorbent resin crosslinked structure (particularly a water absorbent resin crosslinked gel structure), and the water absorbent resin decomposition product is incorporated into the water absorbent resin crosslinked structure (particularly a water absorbent resin crosslinked gel structure). As a result, radicals generated by the decomposition of the hydrogen abstraction type peroxide abstract hydrogen from the decomposition product chains and the crosslinked structure chains, generating polymer radicals. The polymer radicals bond with each other to generate crosslinks, and the decomposition product is incorporated into the crosslinked structure.
[0129] Preferably, the decomposition product is incorporated into the crosslinked structure by carrying out the polymerization step in the presence of a hydrogen abstraction peroxide. More preferably, the decomposition product is incorporated into the crosslinked structure by mixing the decomposition product, the crosslinked structure obtained in the polymerization step, and the hydrogen abstraction peroxide, or by preparing an aqueous monomer solution containing a monomer, the decomposition product, and a hydrogen abstraction peroxide in the monomer aqueous solution preparation step [2-2-1] and subjecting the aqueous monomer solution to the main polymerization step. Particularly preferably, the decomposition product is incorporated into the crosslinked structure (particularly a crosslinked gel structure) by mixing the decomposition product, the crosslinked structure obtained in the polymerization step, and the hydrogen abstraction peroxide. In addition, when a hydrogen abstraction peroxide having a high decomposition temperature is used, crosslinking can be expected not only in the polymerization step but also in the drying step.
[0130] Here, from the viewpoint of more efficient incorporation, the hydrogen abstraction type peroxide is preferably a compound with high hydrogen abstraction ability (hence, radical generation ability). Such a compound allows the decomposition product to be incorporated into the crosslinked structure with a higher probability. Specific examples include t-butylperoxyisopropylcarbonate, t-butylperoxy(2-ethylhexyl)carbonate, t-butylperoxybenzoate, t-butylcumylperoxide, di(t-butylperoxyisopropyl)benzene, 1,1-(t-butylperoxy)3,3,5-trimethylcyclohexane, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexane. These hydrogen abstraction type peroxides may be used alone or in combination of two or more.
[0131] A preferred method for using hydrogen abstraction peroxide is to add the hydrogen abstraction peroxide to an aqueous monomer solution in advance and chemically incorporate the peroxide into the monomer solution simultaneously with polymerization. In addition to the above method, a method of adding hydrogen abstraction peroxide during and / or after polymerization for post-crosslinking can also be used. These methods can also be used in combination.
[0132] The amount of the hydrogen abstraction type peroxide used is preferably 0.010% by mass or more and 10% by mass or less, more preferably 0.050% by mass or more and 5.0% by mass or less, based on the total mass of the water absorbent resin (the total mass of the water absorbent resin being 100% by mass). By setting the amount used within the above range, a desired water absorbent resin can be obtained. With the amount used, the amount of soluble polymer is reduced, and even if the water absorbent resin is produced using a water absorbent resin that should have been discarded, the decrease in water absorption performance (particularly, water absorption capacity under pressure) can be more effectively suppressed.
[0133] [Method iv)] In this method, a photoinitiator and / or a photosensitizer is added to the water-absorbent resin decomposition product and the water-absorbent resin crosslinked structure (particularly a water-absorbent resin crosslinked gel structure), thereby incorporating the water-absorbent resin decomposition product into the water-absorbent resin crosslinked structure (particularly a water-absorbent resin crosslinked gel structure). Here, the photoinitiator and / or the photosensitizer may be combined with ultraviolet irradiation. In this case, the photoinitiator and / or the photosensitizer is decomposed by ultraviolet irradiation, and the generated radicals abstract hydrogen from the decomposition product chain and the crosslinked structure chain, generating a polymer radical. The polymer radicals are bonded to each other to generate a crosslink, and the decomposition product is incorporated into the crosslinked structure.
[0134] Preferably, the decomposition product is incorporated into the crosslinked structure by carrying out the polymerization step in the presence of a photoinitiator and / or a photosensitizer. More preferably, the decomposition product is incorporated into the crosslinked structure by further adding a photoinitiator and / or a photosensitizer to the decomposition product and the crosslinked structure during the polymerization step, or by preparing an aqueous monomer solution containing a monomer, a decomposition product, and a photoinitiator and / or a photosensitizer in the monomer aqueous solution preparation step [2-2-1] and subjecting the aqueous monomer solution to the main polymerization step. Particularly preferably, the decomposition product is incorporated into the crosslinked structure (particularly a crosslinked gel structure) by preparing an aqueous monomer solution containing a monomer, a decomposition product, and a photoinitiator and / or a photosensitizer in the monomer aqueous solution preparation step [2-2-1] and subjecting the aqueous monomer solution to the main polymerization step.
[0135] The photoinitiator or photosensitizer is preferably a compound that decomposes upon irradiation with ultraviolet light to generate radical molecules.Specific examples include benzophenone, acetophenone, fluorenone, benzaldehyde, propiophenone, anthraquinone, carbazole, 3-methylacetophenone, 4-methylacetophenone, 3-methoxybenzophenone, 4-methoxybenzophenone, 4,4'-dimethoxybenzophenone, 4,4'-bis(dimethylamino)benzophenone (Michler's ketone), allylacetophenone, 2,2'-diphenoxyacetophenone, benzoin, methylbenzoin ether, ethylbenzoin ether, benzoin acetate, benzoin phenyl carbamate, benzoin acrylate, benzoin phenyl ether, benzoyl peroxide, dicumyl peroxide, azoisobutyronitrile phenyl disulfide, acylphosphane oxide, and chlorine methylanthraquinone. Among these, benzophenone / amine, Michler's ketone / benzophenone, and thioxanthone / amine are preferred from the viewpoint of particularly excellent hydrogen abstraction properties. These may be used alone or in combination of two or more.
[0136] As a method for using the photoinitiator and / or photosensitizer, a method is preferably applied in which the photoinitiator and / or photosensitizer is added in advance to the monomer aqueous solution, and ultraviolet irradiation is performed simultaneously with polymerization. On the other hand, in addition to the above method, a method of adding the photoinitiator and / or photosensitizer during and / or after polymerization to perform post-crosslinking, etc. can also be adopted. These methods can also be used in combination.
[0137] The amount of the photoinitiator and / or photosensitizer used is preferably 0.010% by mass or more and 10% by mass or less, more preferably 0.050% by mass or more and 5.0% by mass or less, based on the total mass of the water absorbent resin (total mass of the water absorbent resin being 100% by mass). By setting the amount used within the above range, a desired water absorbent resin can be obtained. With the amount used, the amount of soluble polymer is reduced, and even if the water absorbent resin is produced using a water absorbent resin that should be discarded, the decrease in water absorption performance (particularly water absorption capacity under pressure) can be more effectively suppressed.
[0138] [Method v] In this method, the water-absorbent resin decomposition product and the water-absorbent resin crosslinked structure (particularly the water-absorbent resin crosslinked gel structure) are irradiated with radiation, thereby incorporating the water-absorbent resin decomposition product into the water-absorbent resin crosslinked structure (particularly the water-absorbent resin crosslinked gel structure). Polymer radicals are generated on the decomposition product chains and the crosslinked structure chains by irradiation with radiation (e.g., electron beams, gamma rays, X-rays). Crosslinks are generated by bonding between the polymer radicals, and the decomposition product is incorporated into the crosslinked structure. In addition, the polymer radicals react with oxygen in the air to generate diperoxides and hydroperoxides, and the generated polymer radicals bond with each other via these to generate crosslinks, which also incorporates the decomposition product into the crosslinked structure.
[0139] In this case, the radiation irradiation conditions can be appropriately selected so that a desired amount of polymer radicals are generated on the decomposition product chains and the crosslinked structure chains.
[0140] Among the methods i) to v), the methods i) to iii) are preferred, and the method i) is more preferred. Furthermore, the method i) is particularly preferably carried out in the monomer aqueous solution preparation step or the polymerization step.
[0141] [2-2-3] Crushing process This step is a step of gel-pulverizing the crosslinked structure (particularly the crosslinked gel structure) obtained in the polymerization step, for example, with a screw extruder such as a kneader or meat chopper, or a gel pulverizer such as a cutter mill, to obtain a particulate crosslinked structure (hereinafter also referred to as a "particulate crosslinked structure" or a "particulate hydrogel"). When the polymerization step is kneader polymerization, the polymerization step and the gel pulverization step are carried out simultaneously. When a particulate hydrogel is obtained directly in the polymerization process, such as in gas phase polymerization or reverse phase suspension polymerization, the gel pulverization step may not be carried out. When the crosslinked structure obtained in the polymerization step is in the form of a sheet, it may be cut into strips or the like before the gel pulverization.
[0142] As for the gel crushing conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.
[0143] [2-2-4] Drying process This step is a step of obtaining a dry polymer by drying the particulate crosslinked structure (particulate hydrogel) obtained in the polymerization step and / or pulverization step to a desired resin solid content. The resin solid content is determined from the loss on drying (the change in mass when 1 g of the water-absorbent resin is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass.
[0144] The method for drying the particulate hydrogel is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.
[0145] The drying temperature (hot air temperature) in the hot air drying is preferably 120°C or higher and 250°C or lower, more preferably 150°C or higher and 200°C or lower, from the viewpoint of the color tone of the water-absorbent resin, drying efficiency, etc. In addition, the drying conditions other than the drying temperature, such as the wind speed of the hot air and the drying time, may be appropriately set according to the water content and total mass of the particulate hydrogel to be dried and the target resin solid content. When band drying is performed, the various conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, 2011 / 111657, etc. are appropriately applied as drying conditions.
[0146] By setting the above-mentioned drying temperature, drying time, etc., within the above-mentioned ranges, the desired properties (e.g., CRC, water absorption capacity under pressure, water-soluble content, and color tone, particularly water-soluble content) of the obtained water absorbent resin can be set within a desired range.
[0147] By the above operation, the decomposition product of the water-absorbent resin is incorporated inside the water-absorbent resin crosslinked structure (particularly the water-absorbent resin crosslinked gel structure). Hereinafter, the product "in which the decomposition product of the water-absorbent resin is incorporated inside the water-absorbent resin crosslinked structure (particularly the water-absorbent resin crosslinked gel structure)" is also referred to as "embedded water-absorbent resin". Next, it is preferable to carry out a surface crosslinking step on this embedded water-absorbent resin. This can improve the water-absorption properties (particularly the water-absorption capacity under pressure).
[0148] [2-2-5] Surface crosslinking step This step is a step of providing a portion with a higher crosslink density on a surface layer (particularly, a portion several tens of μm from the surface of the water absorbent resin precursor) of the incorporated water absorbent resin obtained through the above-mentioned steps, and can be composed of a mixing step, a heat treatment step, and a cooling step (optional).
[0149] In the surface cross-linking step, a surface-cross-linked water-absorbent resin is obtained by radical cross-linking, surface polymerization, cross-linking reaction with a surface cross-linking agent, or the like on the surface of the incorporated water-absorbent resin.
[0150] (Surface cross-linking agent) The surface cross-linking agent used in one embodiment of the present invention is not particularly limited, but includes organic or inorganic surface cross-linking agents. Among them, from the viewpoint of the physical properties of the water-absorbent resin, the handling property of the surface cross-linking agent, etc., organic surface cross-linking agents that react with carboxyl groups are preferred. For example, one or more surface cross-linking agents disclosed in U.S. Patent No. 7,183,456 can be mentioned. More specifically, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyvalent amine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal compounds, alkylene carbonate compounds, cyclic urea compounds, etc. can be mentioned.
[0151] Specifically, polyhydric alcohol compounds such as ethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, 1,3-propanediol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerin, polyglycerin, 2-butene-1,4-diol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,2-cyclohexanol, trimethylolpropane, diethanolamine, triethanolamine, polyoxypropylene, oxyethylene-oxypropylene block copolymer, pentaerythritol, and sorbitol; ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol Epoxy compounds such as cerol polyglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol polyglycidyl ether, glycidol, sorbitol polyglycidyl ether, pentaerythritol polyglycidyl ether, trimethylolpropane polyglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether; polyamine compounds and inorganic or organic salts thereof such as ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, and polyethyleneimine; polyisocyanate compounds such as 2,4-tolylene diisocyanate and hexamethylene diisocyanate; aziridine compounds such as polyaziridine; polyoxazoline compounds such as 1,2-ethylenebisoxazoline, bisoxazoline, and polyoxazoline; carbonic acid derivatives such as urea, thiourea, guanidine, dicyandiamide, and 2-oxazolidinone;1,3-dioxolan-2-one (ethylene carbonate), 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 4-hydroxymethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4-methyl-1,3-dioxan-2-one, 4,6-dimethyl-1,3-dioxan-2-one, 1,3-dioxopane alkylene carbonate compounds such as dimethyl-2-one; haloepoxy compounds such as epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, and polyvalent amine adducts thereof; oxetane compounds; silane coupling agents such as γ-glycidoxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane; polyvalent metal compounds such as hydroxides, chlorides, sulfates, nitrates, or carbonates of zinc, calcium, magnesium, aluminum, iron, zirconium, and the like; and the like. Among these, two or more may be used in combination. Among the above surface crosslinking agents, one or more selected from polyvalent metal compounds, epoxy compounds, oxazoline compounds, and alkylene carbonate compounds are preferred.;
[0152] The amount of the surface crosslinking agent used (when a plurality of agents are used, the total amount used) is preferably 0.01 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the water-absorbent resin precursor. The surface crosslinking agent is preferably added as an aqueous solution, and in this case, the amount of water used is preferably 0.5 to 20 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the water-absorbent resin precursor. Furthermore, when a hydrophilic organic solvent is used as necessary, the amount used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin precursor.
[0153] In addition, each of the additives to be added in the "rewetting step" described later can be added by mixing it with the surface crosslinking agent (aqueous solution) in an amount of 5 parts by mass or less, or can be added separately in this mixing step.
[0154] (Mixing process) This step is a step of mixing the water-absorbent resin precursor with the surface crosslinking agent. The method of mixing the surface crosslinking agent is not particularly limited, but for example, a method of preparing a surface crosslinking agent solution in advance and mixing the liquid with the water-absorbent resin precursor is preferred. In this case, the surface crosslinking agent solution is mixed with the water-absorbent resin precursor by more preferably spraying or dropping, and more preferably spraying.
[0155] The device for carrying out the mixing is not particularly limited, but is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.
[0156] (Heat treatment process) This step is a step in which heat is applied to the mixture discharged from the mixing step to cause a crosslinking reaction on the surface of the water-absorbent resin precursor.
[0157] The device for carrying out the crosslinking reaction is not particularly limited, but preferably includes a paddle dryer. The reaction temperature in the crosslinking reaction is appropriately set according to the type of surface crosslinking agent used, and is preferably 50°C or more and 300°C or less, more preferably 100°C or more and 200°C or less. The reaction time in the crosslinking reaction is appropriately set according to the water content of the object of the heat treatment process, the type of surface crosslinking agent, the thermal efficiency of the heating device, etc., and it is preferable to heat until the water content becomes 10% by mass or less. For example, the reaction time in the crosslinking reaction is, for example, 10 minutes or more and 120 minutes or less, and preferably 30 minutes or more and 90 minutes or less.
[0158] (cooling process) This step is an optional step that is installed as necessary after the heat treatment step. The cooling device is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. The surface-crosslinked water-absorbent resin obtained in the heat treatment step is forcibly cooled, as necessary, in the cooling step, preferably to 40°C or more and 80°C or less, more preferably to 50°C or more and 70°C or less.
[0159] After the surface cross-linking step, a sizing step may be further carried out. In addition to the above, the method according to the present invention may include at least one step selected from the steps of adding various additives, removing fine powder, recycling fine powder (recovering fine powder), and filling. Furthermore, various known steps may be included depending on the purpose. The fine powder removed in the removing fine powder step may be used as a recovered water absorbent resin.
[0160] [2-2-6] Particle sizing process This step is a step for adjusting the particle size of the surface-crosslinked water-absorbent resin precursor. This particle size adjustment step provides a water-absorbent resin whose particle size or particle size distribution is more actively controlled.
[0161] Preferably, the sizing step includes a crushing step and / or a classification step. The crushing step is a step of adjusting the particle size by crushing the loosely aggregated granular material after the surface cross-linking step with a crusher. The classification step is a step of removing coarse particles and fine powder from the surface cross-linked granular material or the crushed material thereof with a classifier.
[0162] The crusher is not particularly limited, and examples thereof include a vibration mill, a roll granulator, a knuckle type crusher, a roll mill, a high-speed rotary crusher (pin mill, hammer mill, screw mill), a cylindrical mixer, etc. Those that cause little damage to the dried material or the surface-crosslinked dried material are preferred, and specific examples thereof include a roll granulator (Matsubo Corporation), a granulator (Kurimoto Iron Works, Ltd.), and a Randel Mill (Tokuju Corporation). As a classifier, a vibrating or rocking sieve classifier using a sieve net is used.
[0163] [2-2-7] Fine powder recycling process The "fine powder recycling process" means a process in which the fine powder removed in the classification step is supplied to any process as it is or after granulating the fine powder. Preferably, it is a process in which the fine powder or the fine powder granules are fed to a process before the drying process to reuse them. Examples of processes before the drying process include a monomer aqueous solution preparation process, a polymerization process, a pulverization process of the hydrogel after polymerization, and a drying process of the granular hydrogel. The fine powder may be added to these processes as it is, or may be added after swelling and gelling with water or granulating. In addition, water, a crosslinking agent, a binder other than water (e.g., a water-soluble polymer, a thermoplastic resin), a polymerization initiator, a reducing agent, a chelating agent, a coloring inhibitor, etc. may be added together with the fine powder. The preferred amount of fine powder recovery is appropriately set depending on the target particle size.
[0164] [2-2-8] Other processes In addition to the steps described above, the production method according to the present invention may further include a grinding step, a classification step, a rewetting step, a granulation step, a transportation step, a storage step, a packaging step, a keeping step, and the like, as necessary.
[0165] (Other additives) In addition to the surface cross-linking agent and gel fluidizing agent that are optionally used, conventionally known components such as polymer powders (e.g., starches such as tapioca starch acetate), inorganic fine particles, dust inhibitors, dried water-absorbent resins (fine powder), liquid permeability improvers, and reducing agents (e.g., sodium sulfite) can be further added as other additives before or after drying.
[0166] [3] Physical properties of water-absorbent resins as products For the water-absorbent resin obtained by the production method according to the present invention (particularly, a water-absorbent resin in which a surface cross-linking treatment has been applied to an incorporated water-absorbent resin), when the water-absorbent resin is used in an absorbent article, particularly a disposable diaper, it is desirable to satisfy the following [3-1]. In addition to the following [3-1], it is desirable to further satisfy at least one of the following [3-2] and [3-3], it is more desirable to satisfy at least the following [3-2], and it is particularly desirable to further satisfy both the following [3-2] and the following [3-3].
[0167] [3-1] AAP0.3 (water absorption rate under pressure) The absorbent resin produced by the method according to the present invention has an absorbency under pressure (AAP0.3) of 0.3 psi of the absorbent resin obtained by the method for producing the absorbent resin, which is preferably 20.0 g / g or more, more preferably 21.0 g / g or more, and further preferably 24.0 g / g or more. The upper limit is not particularly limited, but is preferably 35.0 g / g or less from the viewpoint of balance with other physical properties.
[0168] [3-2] Decrease rate of AAP0.3 The water absorbent resin produced by the method according to the present invention can suppress the decrease in AAP0.3 (absorption capacity under pressure) compared to a water absorbent resin (reference water absorbent resin) produced in the same manner except that no decomposition product is used. In one embodiment, the AAP0.3 decrease rate of the water absorbent resin produced by the method according to the present invention, particularly the (meth)acrylic acid (salt)-based water absorbent resin or the water absorbent agent containing the water absorbent resin, is 7.0% or less. In one embodiment, the AAP0.3 decrease rate of the water absorbent resin or the water absorbent agent containing the water absorbent resin is 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, or 4.0% or less (lower limit: 0%).
[0169] In this specification, the AAP0.3 reduction rate is the reduction rate of the AAP0.3 (absorption capacity under pressure) of the water absorbent resin relative to the AAP0.3 (absorption capacity under pressure) of the water absorbent resin (reference water absorbent resin) produced in the same manner except that the decomposition product is not used. Specifically, the AAP0.3 reduction rate is a value obtained by determining the AAP0.3 (absorption capacity under pressure) of the water absorbent resin and the reference water absorbent resin, calculating to the second decimal place according to the following formula: AAP0.3 reduction rate = [(AAP0.3 (g / g) of the reference water absorbent resin) - (AAP0.3 (g / g) of the water absorbent resin)] × 100 / (AAP0.3 (g / g) of the reference water absorbent resin), and rounding it off to the first decimal place.
[0170] [3-3] CRC (absorption capacity without pressure) The absorbency without load (CRC) of the water absorbent resin produced by the method according to the present invention, particularly the (meth)acrylic acid (salt)-based water absorbent resin, is usually 5 g / g or more, preferably 15 g / g or more, more preferably 25 g / g or more, even more preferably 30 g / g or more, and particularly preferably more than 30 g / g. There is no particular limit to the upper limit, and a higher CRC is preferable, but from the viewpoint of balance with other physical properties, it is preferably 70 g / g or less, more preferably 50 g / g or less, and even more preferably 40 g / g or less. When the CRC is less than 5 g / g, the absorption amount is small and it is not suitable for use as an absorbent for absorbent articles such as disposable diapers. In addition, when the CRC is more than 70 g / g, the speed of absorbing body fluids such as urine and blood decreases, so it is not suitable for use in disposable diapers with high water absorption speed.
[0171] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.
[0172] The present invention encompasses the following aspects and configurations.
[0173] 1. The method comprises producing a water absorbent resin by using a decomposed product of the water absorbent resin obtained by decomposing the recovered water absorbent resin as a part of a raw material, A method for producing a water-absorbent resin, characterized in that the decomposition product of the water-absorbent resin is incorporated by a chemical method into a crosslinked structure of the water-absorbent resin obtained by polymerizing a monomer constituting the water-absorbent resin as a raw material; 2. The method for producing a water-absorbent resin according to 1 above, wherein the chemical method includes at least one method selected from the group consisting of the following i) to v): i) adding a crosslinking agent capable of reacting with both the decomposition product of the water-absorbent resin and the crosslinked structure of the water-absorbent resin; ii) introducing a double bond into the decomposition product of the water absorbent resin; iii) adding a hydrogen abstraction type peroxide to the decomposition product of the water absorbent resin and the crosslinked structure of the water absorbent resin; iv) adding a photoinitiator and / or a photosensitizer to the water-absorbent resin decomposition product and the water-absorbent resin crosslinked structure; and v) Irradiating the decomposition product of the water-absorbent resin and the crosslinked structure of the water-absorbent resin with radiation.
[0174] 3. Further comprising a surface cross-linking step; The method for producing a water absorbent resin according to 1. or 2. above, wherein the chemical method is carried out before the surface cross-linking step; 4. The method for producing a water absorbent resin according to any one of 1. to 3., wherein the decomposition product of the water absorbent resin is used in an amount of 1 mass % or more and 60 mass % or less based on the total mass of the water absorbent resin; 5. The method for producing a water-absorbent resin according to any one of 1. to 4., wherein the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article. EXAMPLES
[0175] The effects of the present invention will be described using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples, and examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention. In the following examples, unless otherwise specified, operations were performed at room temperature (25°C). Furthermore, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.
[0176] [Reference example 1] A reaction vessel was charged with 244.9 g of acrylic acid, 0.71 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 103.7 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 389.0 g of deionized water, and the mixture was mixed to prepare an aqueous monomer solution (a').
[0177] Next, the monomer aqueous solution (a') was cooled while stirring. When the liquid temperature reached 40.0°C, 100.9 g of a 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (a). At this time, the temperature of the monomer aqueous solution (a) rose to 77.9°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.
[0178] Next, 12.1 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous solution of monomer (a), and the mixture was immediately poured into a stainless steel bat-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The time from the start of the second stage neutralization to pouring the aqueous solution of monomer (a) into the bat-shaped container was 55 seconds, and the bat-shaped container was heated using a hot plate until the surface temperature reached 40° C. The polymerization reaction started 70 seconds after the aqueous solution of monomer (a) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than that of the bat-shaped container. After 3 minutes had passed since the start of the polymerization reaction, a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") (S1) was taken out. The series of operations was carried out in an open-air system.
[0179] The hydrogel (S1) obtained by the polymerization reaction was cut into strips and crushed using a meat chopper with a die diameter of 7.5 mm. The hydrogel (S1) was then spread on a 50-mesh wire net and dried with hot air at 190°C for 60 minutes.
[0180] Next, the mixture was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a water-absorbent resin precursor (S1) in an irregularly pulverized state.
[0181] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin precursor (S1), and the mixture was subjected to heat treatment at 100°C for 45 minutes.
[0182] The mixture was then cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water-absorbent resin (S1). The obtained water-absorbent resin (S1) had a CRC of 35.9 g / g, an AAP0.3 of 29.4 g / g, and a water-soluble content (16-hour value) of 17.1 mass%. The neutralization rate of the obtained water-absorbent resin (S1) was about 73%.
[0183] [Reference example 2] 733.3 parts by mass of deionized water was added to 100.0 parts by mass of the water absorbent resin (S1) obtained in Reference Example 1, and the mixture was left at room temperature for 12 hours or more to prepare a gel-like simulated recovered water absorbent resin (S1'). Then, the entire amount of the simulated recovered water absorbent resin (S1'), 149.3 parts by mass of a 15% by mass aqueous sodium carbonate solution as a pH adjuster, and 6.67 parts by mass of a 30% by mass aqueous hydrogen peroxide solution as a decomposition agent were added to a reaction vessel equipped with an agitator, and the mixture was thoroughly mixed with the agitator.
[0184] Next, the reaction vessel containing the mixture was immersed in a thermostatic bath at 80° C. to initiate the decomposition reaction. 60 minutes after the start of the reaction, it was confirmed that the gel-like matter had been completely solubilized, and a decomposition product (A) was obtained.
[0185] Next, 80.7 parts by mass of a 15% by mass aqueous solution of sodium carbonate was added to the aqueous solution of the decomposition product (A), and the mixture was stirred at 80° C. for 60 minutes, and then cooled to room temperature. This operation removed hydrogen peroxide remaining in the aqueous solution of the decomposition product (A).
[0186] The resulting aqueous solution of the decomposition product (A) had a solid concentration of 9.24% by mass. The mass average molecular weight Mw of the decomposition product (A) was 483,000.
[0187] [Example 1] (Monomer aqueous solution preparation process) A reaction vessel was charged with 220.4 g of acrylic acid, 0.56 g (0.035 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 324.7 g of the decomposition product (A) obtained in Reference Example 2, 0.27 g (0.050 mol % relative to the carboxyl group-containing unsaturated monomer) of ethylene glycol diglycidyl ether as an external crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 25.2 g of deionized water, and the mixture was mixed to produce an aqueous monomer solution (1').
[0188] Next, the monomer aqueous solution (1') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (1). At this time, the temperature of the monomer aqueous solution (1) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to form a transparent homogeneous solution.
[0189] (Polymerization process) Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous monomer solution (1), and the mixture was immediately poured into a stainless steel bat-shaped container in an open-air system. The time from the start of the second stage neutralization to the pouring of the aqueous monomer solution (1) into the bat-shaped container was 55 seconds, and the bat-shaped container was heated using a hot plate until the surface temperature reached 40°C. The polymerization reaction started 65 seconds after the aqueous monomer solution (1) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. The hydrogel (1) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.
[0190] (Crushing process, drying process) The hydrogel (1) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm. The hydrogel (1) was then spread on a 50-mesh wire net and dried with hot air at 190°C for 60 minutes.
[0191] Next, the mixture was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a water-absorbent resin precursor (1) in an irregularly pulverized form.
[0192] (Surface crosslinking process) 100 parts by mass of the obtained water absorbent resin precursor (1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100°C for 45 minutes.
[0193] Thereafter, the mixture was cooled and passed through a JIS standard sieve with an opening of 710 μm to obtain a water absorbent resin (1). The obtained water absorbent resin (1) had a CRC of 36.1 g / g, an AAP0.3 of 28.1 g / g, and a water-soluble content (16-hour value) of 20.3 mass%.
[0194] [Example 2] (Monomer aqueous solution preparation process) A reaction vessel was charged with 220.4 g of acrylic acid, 0.56 g (0.035 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 324.7 g of the decomposition product (A) obtained in Reference Example 2, 0.53 g (0.100 mol % relative to the carboxyl group-containing unsaturated monomer) of ethylene glycol diglycidyl ether as an external crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 25.2 g of deionized water, and the mixture was mixed to produce an aqueous monomer solution (2').
[0195] Next, the monomer aqueous solution (2') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (2). At this time, the temperature of the monomer aqueous solution (2) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to form a transparent homogeneous solution.
[0196] (Polymerization process) Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous monomer solution (2), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second stage neutralization to the pouring of the aqueous monomer solution (2) into the vat-type container was 55 seconds, and the vat-type container was heated using a hot plate until the surface temperature reached 40°C. The polymerization reaction started 65 seconds after the aqueous monomer solution (2) was poured into the vat-type container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the vat-type container. The hydrogel (2) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.
[0197] (Crushing process, drying process) The hydrogel (2) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm. The hydrogel (2) was then spread on a 50-mesh wire net and dried with hot air at 190°C for 60 minutes.
[0198] Next, the mixture was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a water-absorbent resin precursor (2) in an irregularly pulverized state.
[0199] (Surface crosslinking process) 100 parts by mass of the obtained water absorbent resin precursor (2) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to heat treatment at 100°C for 45 minutes.
[0200] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water absorbent resin (2). The obtained water absorbent resin (2) had a CRC of 35.2 g / g, an AAP0.3 of 28.8 g / g, and a water-soluble content (16-hour value) of 18.1 mass%.
[0201] [Comparative Example 1] (Monomer aqueous solution preparation process) A reaction vessel was charged with 220.4 g of acrylic acid, 0.64 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 324.7 g of the decomposition product (A) obtained in Reference Example 2, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 25.2 g of deionized water, and the mixture was mixed to produce an aqueous monomer solution (C1').
[0202] Next, the monomer aqueous solution (C1') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (C1). At this time, the temperature of the monomer aqueous solution (C1) rose to 78.1°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.
[0203] (Polymerization process) Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous monomer solution (C1), and the mixture was immediately poured into a stainless steel bat-shaped container in an open-air system. The time from the start of the second stage neutralization to the pouring of the aqueous monomer solution (C1) into the bat-shaped container was 55 seconds, and the bat-shaped container was heated using a hot plate until the surface temperature reached 40°C. The polymerization reaction started 70 seconds after the aqueous monomer solution (C1) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than that of the bat-shaped container. The hydrogel (C1) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.
[0204] (Crushing process, drying process) The hydrogel (C1) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm. The hydrogel (C1) was then spread on a 50-mesh wire net and dried with hot air at 190°C for 60 minutes.
[0205] Next, the mixture was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a water-absorbent resin precursor (C1) in an irregularly pulverized state.
[0206] (Surface crosslinking process) 100 parts by mass of the obtained water absorbent resin precursor (C1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100°C for 45 minutes.
[0207] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a comparative water absorbent resin (C1). The comparative water absorbent resin (C1) thus obtained had a CRC of 36.4 g / g, an AAP0.3 of 27.2 g / g, and a water-soluble content (16-hour value) of 25.0 mass%.
[0208] [Comparative Example 2] (Monomer aqueous solution preparation process) A reaction vessel was charged with 220.4 g of acrylic acid, 0.64 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 324.7 g of the decomposition product (A) obtained in Reference Example 2, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 25.2 g of deionized water, and the mixture was mixed to produce an aqueous monomer solution (C2').
[0209] Next, the monomer aqueous solution (C2') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (C2). At this time, the temperature of the monomer aqueous solution (C2) rose to 78.4°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.
[0210] (Polymerization process) Next, 10.9 g of 4.0% by mass sodium persulfate aqueous solution was added to the stirred monomer aqueous solution (C2), and immediately poured into a stainless steel bat-shaped container in an open-air system. The time from the start of the second stage neutralization to pouring the monomer aqueous solution (C2) into the bat-shaped container was 55 seconds, and the bat-shaped container was heated using a hot plate until the surface temperature reached 40°C. The polymerization reaction started 65 seconds after the monomer aqueous solution (C2) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. The hydrogel (C2) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.
[0211] (Crushing process, drying process) The hydrogel (C2) obtained by the polymerization reaction was cut into strips and crushed using a meat chopper with a die diameter of 7.5 mm. The hydrogel (C2) was then spread on a 50-mesh wire net and dried with hot air at 190°C for 60 minutes.
[0212] Next, the mixture was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a water-absorbent resin precursor (C2) in an irregularly pulverized state.
[0213] (Surface crosslinking process) 100 parts by mass of the obtained water absorbent resin precursor (C2) was uniformly mixed with a surface crosslinking agent solution consisting of 0.040 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to heat treatment at 100°C for 45 minutes.
[0214] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a comparative water absorbent resin (C2). The comparative water absorbent resin (C2) thus obtained had a CRC of 35.5 g / g, an AAP0.3 of 27.3 g / g, and a water soluble content (16-hour value) of 24.5% by mass.
[0215] [Table 1]
[0216] (summary) Table 1 shows the physical properties and water-extractable contents (16-hour values) of the water-absorbent resins obtained in Reference Example 1, Examples 1 and 2, and Comparative Examples 1 and 2.
[0217] It is clear from Table 1 that in Comparative Examples 1 and 2, the AAP0.3 decrease rate exceeded 7.0% and the water extractable content (16-hour value) was significantly increased compared to Reference Example 1.
[0218] On the other hand, it is understood that in Examples 1 and 2, the AAP0.3 decrease rate is smaller than in the Comparative Example, and the increase in the water extractable content (16-hour value) is also suppressed.
[0219] From these results, it is considered that in Examples 1 and 2, in which the polymerization process was carried out in the presence of an external crosslinking agent, the crosslinked structure (the crosslinked structure formed by the polymer gel) and the decomposition products were chemically bonded, and the decomposition products were incorporated into the crosslinked structure, thereby reducing the amount of water-soluble matter (16-hour value), and as a result, the decrease in AAP0.3 was suppressed.
[0220] In contrast, Comparative Example 1 is an example in which an external crosslinking agent was not used in the polymerization step, but the increase in the water-soluble content was greater than that of Reference Example 1. This is believed to be because the decomposition products were not sufficiently incorporated into the crosslinked structure (there was little or no chemical bond between the decomposition products and the crosslinked structure). This is believed to be why the decrease in AAP0.3 was also large.
[0221] Comparative Example 2 is an example in which the amount of the surface crosslinking agent used in the surface crosslinking step was increased to 1.33 times that of Reference Example 1 in expectation of improvement / increase in incorporation (chemical bond) of the decomposition product into the crosslinked structure. In this case, however, the effect of suppressing the increase in the water-soluble content was slight, and almost no improvement in AAP0.3 was observed, and it is understood that only increasing the amount of the surface crosslinking agent has little effect.
Claims
1. The method comprises producing a water absorbent resin by using a decomposed product of the water absorbent resin obtained by decomposing the recovered water absorbent resin as a part of a raw material, A method for producing a water-absorbent resin, characterized in that the decomposition product of the water-absorbent resin is incorporated by a chemical method into a crosslinked structure of the water-absorbent resin obtained by polymerizing a monomer constituting the water-absorbent resin as a raw material.
2. The method for producing a water-absorbing resin according to claim 1, wherein the chemical method includes at least one method selected from the group consisting of the following i) to v): i) adding a crosslinking agent capable of reacting with both the decomposition product of the water-absorbent resin and the crosslinked structure of the water-absorbent resin; ii) introducing a double bond into the water absorbent resin decomposition product; iii) adding a hydrogen abstraction type peroxide to the decomposition product of the water absorbent resin and the crosslinked structure of the water absorbent resin; iv) adding a photoinitiator and / or a photosensitizer to the water-absorbent resin decomposition product and the water-absorbent resin crosslinked structure; and v) Irradiating the decomposition product of the water-absorbent resin and the crosslinked structure of the water-absorbent resin with radiation.
3. Further comprising a surface cross-linking step, The method for producing a water-absorbent resin according to claim 1 or 2, wherein the chemical technique is carried out prior to the surface cross-linking step.
4. The method for producing a water-absorbent resin according to claim 1 or 2, wherein the decomposition product of the water-absorbent resin is used in an amount of 1% by mass or more and 60% by mass or less based on the total mass of the water-absorbent resin.
5. The method for producing a water-absorbent resin according to claim 1 or 2, wherein the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article.
Citation Information
Patent Citations
Method for producing water-absorbing resin particles
WO2020213298A1
Method for producing water-absorbing resin particles
WO2022080342A1